Data investigation on the performance-enhancing drugs spread in Italy among young athletes: Prevention trough education and the fight against doping in sport - Mazzeo, F.; Santamaria, S.; Di Onofrio, V. (Journal of Human Sport & Exercise, 2021)
Introduction: Substances and methods capable of improving athletic performance have been one of the greatest concerns in elite sport community. It is a serious danger to sport and health. The teacher, coach and educator play an important role in the "physically" training of educated people and in culture of health promotion. Methodology: The study combines a bibliographic research about education importance in doping prevention and the Italian data analysis in doping spread for attention among young athletes (<19). The bibliographic sources were identified on Scopus, PubMed and ScienceDirect. The data relating about doping spread were extrapolated by reports of the Italian Ministry of Health. The time frame considered from 2018 (latest available data) to 2013. Results: The available data show that 2014 had the highest number of positives (58) and that, starting from that year, the doped athletes number was significantly lower up to 13 in 2018. On young people <19 an almost irrelevant positives number can be seen. Even in 2014 the positives number was 0. Conclusion: This study shows data on the doping prevalence and the result of WADA's identification of educational programs and research on social prevention as strategic priorities for the development of evidence-based anti-doping education.